Hydrogen peroxide detection with a silver nanoparticle grating chip fabricated by plasmonic plating. Issue 23 (28th May 2019) - Yoshikawa, Hiroyuki; Hieda, Kenshiro; Ikeda, Kanako; Tamiya, Eiichi
Abstract : An optical detection of hydrogen peroxide (H2 O2 ) is proposed, using grating structures of silver nanoparticles (AgNPs). Abstract : An optical detection of hydrogen peroxide (H2 O2 ) is proposed, using grating structures of silver nanoparticles (AgNPs). Periodic line structures of AgNPs are deposited on a gold nanoparticle (AuNP)-decorated glass plate using an interference exposure with a green laser beam, based on the plasmonic plating method. This AgNP grating chip diffracts incident light, and the diffraction efficiency is dependent on the amount of AgNPs. By applying a drop of H2 O2 solution onto the chip, the diffraction intensity declines due to the autocatalytic decomposition of AgNPs. A portable measurement system of the diffraction intensity change is constructed, and the H2 O2 detection in the concentration range 6.7–668 μmol L −1 is performed in 2 min simply by dropping the H2 O2 solution onto the substrate.